Unemployment Hysteresis in Turkey: Does Education Matter? - KULA, Ferit; ASLAN, Alper (International Journal of Economics and Financial Issues, 2013)
This paper re-examines the empirical validity of the hysteresis hypothesis in unemployment rates in terms of education level in Turkey with minimum Lagrange Multiplier (LM) unit root methodology. Our empirical findings indicate that the time series properties of high and vocational high school educated unemployment rates are different than the overall unemployment rate and other educational unemployment rates. Keywords: unemployment; business cycles; hysteresis, Turkey JEL Classifications: J21; J64